AN APPRAISAL OF OSUN OSOGBO AS A FESTIVAL THEATRE - Modupe Elizabeth, Olaniyan (European Scientific Journal, ESJ, 2014)
This research looks at a Nigerian festival from the theatrical point ofview. The popular Osun Osogbo festival in the South-Western part of thecountry has been chosen for the purpose. The research looks into the ways inwhich the festival is being celebrated from the beginning to the end, i.e fromthe preparatory aspect of the festival to the actual performance, in terms ofthe day- to - day activities. The research is divided into three parts. The firstpart deals with the account of the various myths surrounding the origin vis-àvisthe worship of River Osun goddess. The second part gives an account ofthe day-to-day activities of the celebration of the festival as witnessed by theresearcher. The third part gives an analysis of the various characteristics of afestival theatre and relates same to Osun festival to see whether it fits intowhat can be called a theatrical performance.The researcher observes that there are theatrical elements likedramatic personae, arena, costume, spectacle, music and dance etc embeddedin the festival and therefore can unequivocably be called a festival theatreThe paper concludes that if the various cultural festivals of Nigeriacould be upgraded to national and international status like the Osun Osogbofestival, they would not only boost the nation‘s tourist attraction, they wouldalso boost the internally-generated revenue of the Nigerian Nation.The paper therefore recommends that the cultural values of thecountry should be annexed to attract international status in order to boost theeconomy of the nation.